2022
DOI: 10.1021/acs.iecr.1c04710
|View full text |Cite
|
Sign up to set email alerts
|

An In-Situ-Grown Cu-BTC Metal–Organic Framework / Graphene Oxide Hybrid Adsorbent for Selective Hydrogen Storage at Ambient Temperature

Abstract: A Cu-BTC metal−organic framework hybrid with graphene oxide (GO) having ultralow GO content (1 wt %) was developed in situ and was explored as a medium for hydrogen storage at ambient temperature. The structural integration of both counterparts in the Cu-BTC/GO hybrid was attained through interaction of the Cu centers with the oxygen-bearing groups of GO by equatorial and axial coordination upon in-situ growth. As a result, Cu-BTC/GO showed enhanced surface area, pore volume, and microporosity, while its hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 67 publications
2
14
0
Order By: Relevance
“…To confirm the successful synthesis of MOF HKUST-1 by three different strategies, the XRD diffractograms were collected for all three materials, as shown in Figure 1. All samples match well with the standard reference patterns and show all the major indexed peaks, 37,38 confirming the formation of the HKUST-1 phase along with a minor impurity peak at 26.67°, which possibly corresponds to copper hydroxide carbonate (JCPDS: 01-072-0539) in all three synthesis strategies. However, HKUST-Ca presents more intense and narrow peaks indicative of higher crystallinity and higher crystal size.…”
Section: Resultsmentioning
confidence: 99%
“…To confirm the successful synthesis of MOF HKUST-1 by three different strategies, the XRD diffractograms were collected for all three materials, as shown in Figure 1. All samples match well with the standard reference patterns and show all the major indexed peaks, 37,38 confirming the formation of the HKUST-1 phase along with a minor impurity peak at 26.67°, which possibly corresponds to copper hydroxide carbonate (JCPDS: 01-072-0539) in all three synthesis strategies. However, HKUST-Ca presents more intense and narrow peaks indicative of higher crystallinity and higher crystal size.…”
Section: Resultsmentioning
confidence: 99%
“…MAA-Fe 3 O 4 NPs exhibits the characteristic FT-IR peak specially at 588 belonged to the Fe–O vibration, a small peak at 2693 cm −1 related to S−H stretching vibration and a sharp peak at 1618 cm −1 as well as a broad peak at 3422 cm −1 attributed to the starching C=O and H–O vibrations of MAA located on the surface of Fe 3 O 4 , respectively ( Bandosz and Petit, 2011 ; Zeng et al, 2013 ). Notably, the peaks at 1090 and 732 cm−1 (C−O−Cu), as well as the other 588 (Fe–O), 1358 (C–O) and 1642 cm −1 (C=O) intensified in the FT-IR spectrum of Fe 3 O 4 @[Cu 3 (BTC) 2 ] indicate the successful formation of Fe 3 O 4 @[Cu 3 (BTC) 2 ] composites ( Varghese et al, 2022 ). The peak intensity was lower in Fe 3 O 4 @[Cu 3 (BTC) 2 ] due to the immobilization caused by coating [Cu 3 (BTC) 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…For H 2 storage area, it has been reported that the doping of carbonaceous materials into MOFs could enhance H 2 uptake via reversible physisorption way owing to its rich sur faceactive sites, power dispersive force, improved H 2 binding enthalpies, and enhanced stability. [173][174][175] For functional materials anchored into MOFs, the functional units usually serve as active centers or performanceenhancing cocatalysts/auxiliaries while the MOFs serve as porous supports to immobilize and confine these materials. Moreover, the strong interplay and synergistic effects between anchored functional materials and MOFs can greatly improve the performance of MOF composites for H2 economy.…”
Section: Compositional Design Of Mof Composites For H 2 Energy Applic...mentioning
confidence: 99%
“…For H 2 storage area, it has been reported that the doping of carbonaceous materials into MOFs could enhance H 2 uptake via reversible physisorption way owing to its rich surface‐active sites, power dispersive force, improved H 2 binding enthalpies, and enhanced stability. [ 173–175 ]…”
Section: Compositional Design Of Mof Compositesmentioning
confidence: 99%